Diagnóstico de pontos críticos no manejo de bovinos leiteiros recém-nascidos e suas mães para aumento do número de bezerras desmamadas e a produtividade de leite - Pichetti, Caio Cezar (2018)
The objective of the present study was to diagnose management and performance factors in crossbred Jersey/Holstein calves and their mothers in the pre and postpartum periods and during the lactation phase, seeking to identify critical points in the breeding system through negligence in the execution of management factors and possible correlations between performance factors. During the research, 13 dairy cows and their 13 daughters were evaluated during the pre and postpartum phases, as well as during suckling with the aid of a questionnaire. The management factors were colostrum intake between two and six hours after birth, navel treatment with iodine in the first hours of life, difficulty during labor, separation of mother and daughter within 72 hours after delivery, regular vermifuge, free access to water and concentrate, place of birth and dried mothers or not 60 days before delivery. The performance factors of the heifers were diagnosed during the lactation phase and involved monthly measurements of body weight (kg) and height at the withers (m). The mean daily gain (kg/day) was stipulated through the weight and days evaluations between birth and weaning. The evaluations of the mothers were performed in the pre and postpartum, consisting of the milk productivity before drying and after delivery. The case study was conducted at Dala Costa property, which is located in the countryside of the city of Pato Branco - PR for a period of 10 months. All heifers had free access to the Tifton 85 (Cynodon dactylon) pasture, received water and concentrated at will, 4L of milk up to 30 days and 2 L until weaning. A Spearman correlation analysis was performed for the performance factors. There were no significant correlations between the variables of milk production before and after delivery and height at the withers at birth and at weaning (p<0.05). However, significant positive correlations were observed between birth weight (p<0.01) ) and weight one and two months after birth, between birth weight one month after birth (P<0.01), height at the withers one month after birth and weight two months after birth. Weight one month after birth also correlated with mean daily gain (p<0.05). However, the height at the withers one month after birth correlated with height at the withers and weight at two months after birth (p<0.01), the weight two months after birth correlated with height at the withers two months after birth and the mean daily gain (p<0.05). There was also a correlation between weight at weaning, days between birth and weaning, and mean daily gain (p<0.05).